Lettering, Alexandra Dock - Ghosh, Ayan (2023)
Construction work on Alexandra Dock commenced in 1904 and was completed in 1914. It was named after Queen Alexandra of Denmark (1844-1925), Empress of India from 1901-1910, and wife of King-Emperor Edward VII. In January 1972, Alexandra Dock was renamed Indira Dock after the then Prime Minister of India, Indira Gandhi (1917-1984).